Description of Hygiene and Sanitation of Restaurants in Bajawa District, East Nusa Tenggara - Maria Yustina Fengi Nono; Mustakim Sahdan; Soni Doke (Lontar : Journal of Community Health, 2021)
A restaurant is a place that provides food and drinks to the public. Therefore, the hygiene and sanitation of the restaurant are vital to ensure the health of that foods and drinks. This study aims to describe the hygiene and sanitation of restaurant according to variables of location and building, sanitation facilities, kitchen, dining room, and food’s storage, food ingredients and fast food, food processing, food ingredients, and fast-food storages, serving of food and equipment used. This study used descriptive with an observational method to all restaurants in Bajawa District from January to February 2020. The sample was 25 restaurants taken using the total sampling technique. The result showed that 100% (25) restaurants in Bajawa District qualified for variables of location and building, food ingredients and food storages, and the equipment used. However, the variable of sanitation facilities showed that 84% (21) of the restaurants were not qualified. Moreover, all sample restaurants (100%) in Bajawa District were not qualified for variables of kitchen, dining room and food storage, food processing, and serving of food. Overall, 56% (14) of restaurants were not qualified for hygiene and sanitation requirements. Therefore, government or related health offices should continuously supervise the implementation of restaurant hygiene and sanitation.